Analysis Of The Impact Of Infrastructure Development On Poverty In The Island Of Sumatra - Nursalam M. A.; Hutapia Hutapia; Purmini Purmini (UNIVED Press, 2024)
This research aims to find out the influence of the development of road infrastructure, education infrastructure, health infrastructure, clean water and electricity on poverty rates on the island of Sumatra, both simultaneously and partially. This research uses quantitative methods in the form of multiple regression analysis with panel data. This type of research is explanatory research, namely testing the relationship between the dependent variable and the independent variable. In this research the data used is secondary data. The data used was obtained from the Badan Pusat Statistik and Kementerian PUPR which includes: data on the percentage of poor people, data on the percentage of roads in a stable condition, data on the ratio of the number of schools per number of students, data on the number of hospitals, data on the ratio of the amount of clean water distributed per number of residents, and data ratio of the amount of electricity distributed per population on the island of Sumatra for the 2014-2022 period. This research uses a random effect model approach analysis. The research results show that simultaneously and partially road infrastructure, education, health, clean water and electricity have an effect on poverty. This shows that, if there is an increase in each infrastructure variable, it can reduce the percentage of poor people on the island of Sumatra.